EFEKTIFITASSTRETCHING EXERCISE DAN PERNAFASAN YOGA TERHADAP REGULASI TEKANAN DARAH DAN KUALITAS HIDUP KLIEN ESRD YANG MENJALANI HEMODIALISIS DI RUMKITAL DR. RAMELAN SURABAYA - Muji Astuti, Nur; Sudiana, I Ketut; Haryanto, Joni (Unusa Press, 2017)
Hypertension intradialytic can affect the quality of life and quality of life can affect hypertension too. An area of concern to nurses is related to non-pharmacological treatment to prevent the occurrence of intradialitic hypertension and improved quality of life. One of them is with stretching exercise and yoga breathing. This research used quasi experimental pre post control group design design, sample size was 28 ESRD clients intradialysis in Dr. Rumkital. Ramelan Surabaya. Sampling technique used purposive sampling. Variables in this study were stretching exercise, yoga breathing, stretching exercise modification and yoga breathing, systolic blood pressure, diastolic blood pressure, and quality of life. Data collection using mercury sygmomanometer, and KDQOL SF 1.3 questionnaire. Data were analyzed using paired t test and multiple linear regression. The results of this study showed that the most effective intervention for lowering blood pressure 27,143 mmHg is a combination of stretching exercise and respiratory yoga, whereas the most effective yoga breathing improves the quality of life 5,143. ESRD clients intradialysis are expected to remain active in applying stretching exercises and breathing yoga during hemodialysis, and for nurses is expected to increase client motivation as well as arrange a daily program and actively involved in applying stretching exercise and yoga breathing. Key Word: Stretching Exercise, Yoga Breathing, Blood pressure, Quality Of Life